THE EFFECTS OF ACIDIC SPORTS DRINKS ON SURFACE MICROHARDNESS OF DENTAL DIRECT RESTORATIVE MATERIALS AMONG ATHLETES - Gamen Luisa-Cristiana; Țehaniuc Teona-Alexandra; Tărăboanță-Gamen Andra-Claudia (Sport şi Societate)
The presentstudyevaluatedthe erosive potential of sportsdrinks on direct restorative materials used in dentistry. Given the popularity of these beverages and the frequency of tooth exposure to acids, the research aims to assess their impact on the durability and integrity of composite materials used in dental restorations. Material and method: 60 disc-shaped dental composite samples were divided into three groups according to the used material: Group A -GC G-Aenial Universal Flo flowablecomposite resin, Group B -bulk-fill G-Aenial Bulk Injectable composite resin and Group C -G-Aenial Direct Posterior nano-hybrid composite resin.The samples were immersed in acid solutions (Red Bull, Gatorade, Optimum Nutrition Pre-Workout)for 30 minutes, once a day, 28 days. Microhardness was determined by measuring the diagonal of the indentation and was expressed as Vickers hardness number. The obtained data was statistically analyzed using ANOVA One-way and Bonferroni post-hoc tests, with a significance level of 0.05.Findings: The obtained resultsafter submersion in RedBull solutionshowed differences between groups A and B (p=0.016); after submersion in Gatorade, differences were recorded between groups A and C (p=0.003), respectivelyB and C (p=0.039). Submersion in Pre-Workout drinkproducedsignificant differences between groups A and C (p=0.032). Conclusions: The submersion of resins-basedrestorative materials in Red Bull and Pre-Workout solutions significantly reduced the surface microhardness values. The surface microhardness of dental flowable composite resin is particularly affected by exposure to acidic sportsdrinks used by athletes such as Red Bull, ON Pre-Workout and Gatorade.